1988
DOI: 10.1143/jjap.27.l1221
|View full text |Cite
|
Sign up to set email alerts
|

Phase Compatibility and Superconductivity of Y-Ba-Cu-O Compounds

Abstract: Superconducting properties of Y-Ba-Cu-O compounds were investigated in relation to precipitation of second phases. Contour lines of J c, T c and diamagnetic signal intensities were presented in the YO1.5-BaO-CuO system. These superconducting properties decreased steeply with BaCuO2 precipitation, and the maximum J c was obtained in the yttrium-rich composition of Y1.2Ba2Cu3O7-y . It is considered, therefore, that the BaCuO2 precipitating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Therefore, Ag addition may be either advantageous or disadvantageous depending on the Ag distribution within the sample and its degree of dissolution in the other raw materials. This is in agreement with previous studies [6,11] in which the role of Ag was reported to be strongly dependent on the processing techniques and their liquid-forming temperatures. If Ag is to be used as an effective sintering and microstructural aid for YBa 2 Cu 3 O 7−y superconductors, then it is crucial that the initial liquid-formation temperature be lowered, through control of the starting materials, to below the Ag melting point (961…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, Ag addition may be either advantageous or disadvantageous depending on the Ag distribution within the sample and its degree of dissolution in the other raw materials. This is in agreement with previous studies [6,11] in which the role of Ag was reported to be strongly dependent on the processing techniques and their liquid-forming temperatures. If Ag is to be used as an effective sintering and microstructural aid for YBa 2 Cu 3 O 7−y superconductors, then it is crucial that the initial liquid-formation temperature be lowered, through control of the starting materials, to below the Ag melting point (961…”
Section: Resultssupporting
confidence: 93%
“…The reproducibility of composition and physical properties of the melt-textured YBa 2 Cu 3 O 7−y samples was poor even after the addition of Ba to the initial raw materials (composition f) sintered on alumina substrates. Addition of BaCuO 2 to the raw materials to compensate for Ba depletion was not successful because the BaCuO 2 easily forms a secondary phase which tends to accumulate at the grain boundary and consequently impedes the YBa 2 Cu 3 O 7−y grain growth [6]. This result is contradictory to a previous study in which addition of BaCuO 2 in the raw materials could be used as a catalyst for YBa 2 Cu 3 O 7−y grain growth [7].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Because the detrimental effect of grain boundaries on the current percolation is limited to lower operation temperature and magnetic fields below H Fig.32a) [94]. …”
Section: Intragrain Pinning Improvementmentioning
confidence: 99%